Pengaruh Size, Return On Asset dan Leverage Terhadap Islamic Social Reporting (Studi Empiris pada Bank Umum Syariah di Indonesia Tahun 2015-2019) - Yamanhar Zubki (Jurnal Ilmiah Ekonomi Islam, 2022)
Islamic Social Reporting Is a standard for reporting corporate social performance based on Islamic sharia. Born from reporting standards based on AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) an international Islamic financial regulatory institution which was later developed in various countries. In particular, this index is an extension of social performance reporting standards, not only the role of companies in a country's economy but also public expectations about social justice related to the environment, minority and employee rights and the role of companies from a spiritual perspective. There are several factors that influence Islamic Social Reporting, including company size, company profitability and company debt. Based on the results of the study, it can be concluded that partially, first, variable size has a positive influence on Islamic Social Reporting for Islamic Commercial Banks in Indonesia. Second, Return on Assets has no effect on Islamic Social Reporting for Islamic Commercial Banks in Indonesia. Third, Variable Leverage has an influence on Islamic Social Reporting for Islamic Commercial Banks in Indonesia. Meanwhile, the simultaneous issuance of Size, Return on Assets and Leverage has a positive and significant impact on Islamic Social Reporting for Islamic Commercial Banks in Indonesia.